P55 Nurses' understanding and perspectives of advance care planning in COPD. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Kelly, C; Cornally, N
Abstract : Background: Advance care planning (ACP) presents as a current issue within an Irish context. Recent publications by The Irish Hospice Foundation include documents 'Think Ahead' and 'Planning for the Future with COPD'. In 2015 The Assisted Decision-Making Capacity Act was published. Currently, the HSE are in the process of publishing professional guidelines for practice in relation to ACP (HSE 2018.) Much of the existing literature relates to physician's views on ACP in COPD. Articles relating to nurse's understanding of ACP entail more towards other patient subgroups such as oncology patients and the older adult. Method: A descriptive qualitative design was used. Eight staff nurses from a respiratory unit were recruited. Semi-structured interviews were audio-recorded. A topic guide from a previous study was adapted. Results: Four categories were identified; the importance of ACP in COPD, facilitators to ACP in COPD, barriers to ACP in COPD and the role of the nurse. Each category was further subcategorised. Conclusion: Nurses identified the importance of ACP in COPD. Benefits included symptom specific factors but also an improvement in the overall quality of care patients could receive. A number of facilitating factors and challenges were identified by the sample in the provision of ACP. Nurses identified themselves as playing an important and broad role in ACP. Future implications were identified for education, research and practice. Recommendations include an increase in education across both undergraduate and postgraduate forums, further research and the appointment of lead nurses in relation to ACP in COPD patients.